The evolution of the MasAgro hubs: responsiveness and serendipity as drivers of agricultural innovation in a dynamic and heterogeneous context. Issue 5 (19th October 2016) - Camacho-Villa, Tania Carolina; Almekinders, Conny; Hellin, Jon; Martinez-Cruz, Tania Eulalia; Rendon-Medel, Roberto; Guevara-Hernández, Francisco; Beuchelt, Tina D.; Govaerts, Bram
ABSTRACT: Purpose : Little is known about effective ways to operationalize agricultural innovation processes. We use the MasAgro program in Mexico (which aims to increase maize and wheat productivity, profitability and sustainability), and the experiences of middle level 'hub managers', to understand how innovation processes occur in heterogeneous and changing contexts. Design/methodology/approach : We use a comparative case study analysis involving research tools such as documentary review, key informant interviews, focus group discussions, and reflection workshops with key actors. Findings : Our research shows how a program, that initially had a relatively narrow technology focus, evolved towards an innovation system approach. The adaptive management of such a process was in response to context-specific challenges and opportunities. In the heterogeneous context of Mexico this results in diverse ways of operationalization at the hub level, leading to different collaborating partners and technology portfolios. Practical implications : MasAgro experiences merit analysis in the light of national public efforts to transform agricultural advisory services and accommodate pluralistic agricultural extension approaches in Latin America. Such efforts need long-term coherent macro level visions, frameworks and support, while the serendipitous nature of the process requires meso-level implementers to respond and adapt to and move the innovation process forward. Originality/value : This paper contributes to the debate on how to operationalize large programs by showing that the innovation support arrangements enacted in the field should allow for diversity and have a degree of flexibility to accommodate heterogeneous demands from farmers in different contexts as well as continuous changes in the politico- institutional environment.